Role of Empathetic Engineering in Building More Resilient Green Economy Case Study on Creating Resilient Self Sufficient Food Security Programs in Middle East - Buheji, Mohamed (Advances in Social Sciences Research Journal, 2018)
This paper targets to investigate the influence of empathetic engineering on creating more resilience economy driven government organisation structure that delivers the socio-economic needs of the stakeholders effectively. The application of empathetic engineering is carried out by the researcher for establishing a self-sufficiency program that meant to ensure food security for a middle eastern country over a period of three years. The program covered all the farms and gardens in the specified country. The empathetic assessment helped to optimise the designing process and the integration of different jobs through understanding the best alternatives in structuring the organisation. The country benefited from establishing an integrated system and a greener economy intention that would influence the GDP and develop the country’s business model in relevance to food security. The outcome of the empathetic engineering is discussed in relevance on how it created more society development, causing better resilient cost centre business models that are independent of government support yet competitive and productive.